Financial Access and MSMEs Performance during Pandemic COVID-19: The Moderating Role of Digitization - Dewi, Nurma Gupita; Ridhasyah, Rizki; Wibawa, Tio Anta (Universitas Airlangga, 2023)
The Micro Small and Medium Enterprises (MSMEs) sector is critical pillars of the Indonesian economy. The COVID-19 pandemic has had a negative impact on MSMEs. The existence of activity violation policies, namely lockdown and social distancing, needs to be anticipated by MSME actors because it has changed consumer behavior and business competition. Digital transformation is a solution for MSMEs to survive the COVID-19 pandemic. The objective of this study is to investigate the impact of access to finance on MSME performance moderated by digitalization. This study utilized 83 MSMEs as a sample. Data was collected by distributing questionnaires to MSME owners who were selected as research samples. Data analysis was performed using the Moderated Regression Analysis (MRA) method. The results of the study indicated that digitization significantly strengthens the relationship between financial access and MSME performance. For MSME actors, digitization will also make it simpler to introduce products, boost turnover, and assist with recording and producing financial reports.